Palladium-based composite metal oxide semiconductor material, preparation method thereof and hydrogen sensor

By using palladium-based composite metal oxide semiconductor materials in hydrogen sensors, the problems of high power consumption, poor selectivity and insufficient stability in the detection of low-concentration hydrogen in the prior art are solved, and a more efficient and stable hydrogen detection effect is achieved.

CN119640086AActive Publication Date: 2025-03-18CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411829640.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-12
Publication Date
2025-03-18
Estimated Expiration
2044-12-12

AI Technical Summary

Technical Problem

Existing hydrogen sensors have problems such as high power consumption, poor selectivity and insufficient stability when detecting low-concentration hydrogen, which limits its practical application.

Method used

A palladium-based composite metal oxide semiconductor material is used to prepare a composite metal oxide matrix by hydrothermal method, and the palladium element is uniformly supported on the substrate by impregnation method to form a palladium-based composite metal oxide semiconductor material. This material optimizes the mass ratio of tin dichloride, nickel nitrate and palladium chloride, and combines the addition of urea to form a specific porous structure, improving gas-sensitive performance.

Benefits of technology

The low-concentration hydrogen detection capability of hydrogen sensors has been significantly improved, the response time and recovery time have been shortened, and the detection stability and selectivity have also been significantly improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119640086A_ABST
    Figure CN119640086A_ABST
Patent Text Reader

Abstract

The invention provides a palladium-based composite metal oxide semiconductor material, a preparation method thereof and a hydrogen sensor, and the preparation method of the palladium-based composite metal oxide semiconductor material comprises the following steps: carrying out a hydrothermal reaction on stannous chloride, urea and nickel nitrate in deionized water, separating the material, and drying to obtain a composite metal oxide; dispersing the composite metal oxide in deionized water, and then adding palladium chloride and a reducing agent for reaction; and separating and drying the reacted material to obtain the palladium-based composite metal oxide semiconductor material. Wherein the mass ratio of the stannic chloride to the nickel nitrate to the palladium chloride is (17 to 100) to (0.05 to 3) to 1; the mass ratio of the stannic chloride to the urea is 1: (0.2-1). The prepared palladium-based composite metal oxide semiconductor material is high in hydrogen-sensitive selectivity, capable of rapidly detecting hydrogen with low hydrogen concentration, excellent in detection stability and capable of being widely used for preparing hydrogen sensors.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of gas sensors, and in particular to a palladium-based composite metal oxide semiconductor material and a preparation method thereof, and a hydrogen sensor. Background Art

[0002] Hydrogen energy has the advantages of high combustion efficiency and no pollution. It is known as one of the three new energy sources along with solar energy and nuclear energy. As an ideal and efficient fuel, hydrogen energy has been widely used in rocket launches, space shuttles, missiles, fuel vehicles, etc. Although the application of hydrogen energy is becoming more and more extensive, the public's doubts about the safety of hydrogen energy have always accompanied its emergence and development.

[0003] Hydrogen is a colorless, odorless, flammable, explosive, and easily permeable and diffusible hazardous gas. It has an extremely low density, a high diffusion coefficient, and a lower explosion limit of only 4% in the air. It is easy to explode due to leakage during storage, transportation, and use. In recent years, hydrogen leakage and explosion accidents have occurred frequently, causing social concern. Hydrogen sensors used to monitor hydrogen leaks in real time are a necessary condition to ensure the safe use of hydrogen energy, and are of great significance for the storage and real-time monitoring of hydrogen.

[0004] Among the numerous hydrogen sensors, small portable gas sensors have shown outstanding advantages and achievements in trace gas detection. Metal oxide semiconductor (MOS) gas sensors have great application prospects in trace gas detection due to their excellent stability, high sensitivity and easy maintenance. Among them, tin dioxide (SnO2), as a wide bandgap n-type MOS, is considered to be a promising sensing material due to its low cost, simple manufacturing process and good long-term stability. It has been successfully developed and widely used to detect trace hazardous gases. However, SnO2-based gas sensors still have many disadvantages such as high power consumption and poor selectivity, which greatly limit the practical application of gas sensors; in addition, how to further improve the stability of SnO2-based gas sensors has always been a hot topic in the industry. Summary of the invention

[0005] In view of the deficiencies in the prior art, the present invention discloses a palladium-based composite metal oxide semiconductor material and a preparation method thereof, and a hydrogen sensor. The hydrogen sensor comprising the palladium-based composite metal oxide semiconductor material has good stability and can detect low-concentration hydrogen quickly and highly selectively.

[0006] In order to achieve the above technical objectives, on the one hand, the present invention provides a method for preparing a palladium-based composite metal oxide semiconductor material, which comprises the following steps: (1) separating and drying the materials after hydrothermal reaction of tin dichloride, urea and nickel nitrate in deionized water to obtain a composite metal oxide; (2) dispersing the composite metal oxide in deionized water, and then adding palladium chloride and a reducing agent to react; the materials after the reaction are separated and dried to obtain the palladium-based composite metal oxide semiconductor material; wherein the mass ratio of the tin dichloride, the nickel nitrate and the palladium chloride is (17-100): (0.05-3): 1; the mass ratio of the tin dichloride to the urea is 1: (0.2-1).

[0007] The palladium-based composite metal oxide semiconductor material prepared by the above technical scheme uses a composite metal oxide including an n-type semiconductor tin oxide and a p-type semiconductor nickel oxide as a matrix, and palladium is doped into the matrix, which can obtain at least two advantages: (1) a rich heterojunction barrier is formed between tin oxide, nickel oxide and palladium element. Specifically, the semiconductor materials tin oxide and nickel oxide have different electron affinities and energy band structures, and the interface between the two will form a heterojunction; in addition, although palladium is not a semiconductor, it can form a Schottky barrier or ohmic contact with the semiconductor materials tin oxide and nickel oxide, respectively, thereby increasing the prepared palladium-based composite metal oxide by synergistic optimization. The number of heterojunctions in the semiconductor material increases, that is, the number of carrier transfer channels increases, further significantly improving the gas sensing performance of the composite metal oxide; (2) Palladium is a hydrogen-sensitive material with a specific selective characteristic, but its stability is poor and its sensitivity is limited; in the above technical scheme, a hydrothermal method is used to prepare the composite metal oxide matrix, and then the palladium element is uniformly loaded on the composite metal oxide matrix by an impregnation method, so that the overflow effect of the palladium element can be utilized. When hydrogen molecules contact the palladium surface and are adsorbed and dissociated into hydrogen atoms, the hydrogen atoms quickly overflow to the surface of the composite metal oxide to participate in the oxidation-reduction reaction, thereby enhancing the response of the overall composite metal oxide semiconductor material to hydrogen and improving the hydrogen sensitivity selectivity.

[0008] In the above technical scheme, the dosage of the reaction raw materials tin dichloride, nickel nitrate and palladium chloride is optimized, which not only promotes the formation of the heterojunction barrier, but also regulates the loading amount of palladium in the palladium-based composite metal oxide semiconductor material to be between 0.5% and 4%, so that the preparation method of the present invention can improve the hydrogen-sensitive performance of the composite metal oxide semiconductor material by only loading an appropriate and small amount of palladium metal, so that the detection limit is lower and the stability is higher.

[0009] The above technical solution can add urea in an amount of 0.2-1 times the mass of tin dichloride, which can serve as a structure directing agent and reaction regulator in the early stage of the hydrothermal reaction to guide the formation of a specific composite metal oxide nanostructure, and decompose and evaporate after the hydrothermal reaction, so that the composite metal oxide forms a specific porous structure to provide more gas adsorption sites and improve the hydrogen detection sensitivity of the composite metal oxide semiconductor material.

[0010] In a further example of the present invention, the mass ratio of the tin dichloride, the nickel nitrate, and the palladium chloride is explored and optimized. Based on a large amount of experimental data, the mass ratio of the tin dichloride, the nickel nitrate, and the palladium chloride is preferably (17-50): (0.05-1.5): 1, and the semiconductor gas-sensitive material obtained by doping an appropriate amount of palladium in the SnO2 / NiO composite metal oxide shows better hydrogen sensitivity; the palladium-based composite metal oxide semiconductor material is applied to the hydrogen sensor, and the detection limit is lower and the detection stability is higher. In some preferred examples of the present invention, the mass ratio of the tin dichloride, the nickel nitrate, and the palladium chloride is further preferably (17-35): (0.5-1): 1, and further preferably 32: 1: 1, which is conducive to further reducing the detection limit of the obtained palladium-based composite metal oxide semiconductor material, and reducing the response time and recovery time, and improving the stability of the response.

[0011] In a further example of the present invention, the mass ratio of tin dichloride to urea is 1:(0.3-0.5), which further promotes the improvement of the comprehensive hydrogen-sensitive performance of the prepared palladium-based composite metal oxide semiconductor material.

[0012] The purpose of using deionized water in step (1) of the present invention is to use it as a solvent to dissolve the raw materials. Those skilled in the art can set the amount of deionized water in step (1) as needed. For example, preferably, the mass ratio of deionized water to tin dichloride in step (1) is (15-100):1, so as to fully dissolve the reaction raw materials such as tin dichloride, nickel nitrate and urea.

[0013] In a further example of the present invention, the temperature of the hydrothermal reaction in step (1) is 100-150°C, preferably (100-130°C), and the reaction time is 10-15h.

[0014] It should be noted that the present invention is not limited to the device for carrying out the hydrothermal reaction. For example, it is preferably carried out in a high-pressure reactor, a polytetrafluoroethylene-lined reactor or a stainless steel reactor. Those skilled in the art can choose according to their needs, and the scope of protection of the present invention is not limited thereby.

[0015] In a further example of the present invention, the separation operation in step (1) may be centrifugal washing, the rotation speed of the centrifugal washing is 3500-5000 rpm, the washing time is 5-15 min, and the washing is performed 3-5 times.

[0016] In a further example of the present invention, the drying operation in step (1) is carried out in an oven, preferably at 60-80° C. for 10-20 h under air conditions.

[0017] In a further example of the present invention, the mass ratio of the palladium chloride to the reducing agent is 1: (0.5-3), so that the appropriate amount of palladium is uniformly doped in the SnO2 / NiO composite metal oxide through the action of the reducing agent, and the hydrogen detection performance of the overall gas-sensitive material is improved by the overflow effect of palladium metal in hydrogen detection. Preferably, the reducing agent is ascorbic acid or sodium borohydride. In some preferred examples of the present invention, the mass ratio of the palladium chloride to the reducing agent is 1: (0.5-2).

[0018] The purpose of using deionized water in step (2) of the present invention is to disperse the reaction materials and use it as a solvent. Those skilled in the art can set a suitable amount of deionized water as needed. For example, preferably, the mass ratio of deionized water in step (2) to tin dichloride used in step (1) is (15-200):1, so as to facilitate the full dispersion of the composite metal oxide in the deionized water.

[0019] In a further example of the present invention, the reaction in step (2) is carried out under stirring conditions, the reaction temperature is 20-25°C, and the reaction time is 5-10h. The specific operation is preferably carried out in a magnetic stirrer to promote the uniformity of palladium doping.

[0020] The present invention is not limited to the specific process of separation and drying of the material after the reaction in step (2). The separation operation can be selected as centrifugal washing, and the centrifugal washing is preferably carried out at a centrifugal washing speed of 6000-10000 rpm, a washing time of 5-20 min, and 3-5 washings; the drying operation is preferably carried out in an oven, preferably at 60-90° C. for 8-12 h under air conditions.

[0021] On the other hand, the present invention provides a palladium-based composite metal oxide semiconductor material prepared by the above preparation method. In a further example of the present invention, the palladium loading, average particle size and particle size distribution of the composite metal oxide semiconductor material are explored and optimized.

[0022] Furthermore, the palladium loading of the palladium-based composite metal oxide semiconductor material is preferably 0.5%-4%. The palladium-based composite metal oxide semiconductor material of the present invention is uniformly loaded with a small amount of palladium metal, and the overflow effect of the palladium metal is synergistically optimized with the heterojunction barrier of SnO2 and NiO in the composite metal oxide, thereby improving the hydrogen-sensitive performance of the overall semiconductor material. In some preferred embodiments of the present invention, the palladium loading of the palladium-based composite metal oxide semiconductor material is 1.5%-4%; in some preferred examples of the present invention, the palladium loading of the composite metal oxide semiconductor material is further preferably 2.3%-4%, and in some preferred examples of the present invention, the palladium loading of the palladium-based composite metal oxide semiconductor material is further preferably 2.3%, further improving the hydrogen-sensitive performance of the material.

[0023] Furthermore, the average particle size of the composite metal oxide semiconductor material is 80-120 nm, and the particle size distribution is uniform. It is not only easy to separate and purify during the preparation process, but also has a uniform particle size distribution, which is conducive to processing and use, and a hydrogen sensor with stable performance is prepared.

[0024] On the other hand, the present invention provides a hydrogen sensor comprising the above palladium-based composite metal oxide semiconductor material.

[0025] Furthermore, the hydrogen detection lower limit of the hydrogen sensor is 0.5 ppm, the response time is 2-22 s, the recovery time is 4-25 s, and the response stability error of the hydrogen sensor for 30 days is controlled within 10%.

[0026] Furthermore, the hydrogen sensor is obtained by coating a mixed slurry containing the palladium-based composite metal oxide semiconductor material on the outer wall of a ceramic tube having an electrode and drying the mixture; wherein the mixed slurry is obtained by dispersing the palladium-based composite metal oxide semiconductor material in deionized water.

[0027] Furthermore, the coating thickness of the palladium-based composite metal oxide semiconductor material is 50-150 μm.

[0028] Furthermore, the hydrogen sensor further comprises a sensor base for supporting a ceramic tube having an electrode. Optionally, the electrode is an Au electrode, and the ceramic tube is an Al2O3 ceramic tube. Optionally, the drying operation uses a heating resistance wire to heat stably for about 24 hours.

[0029] Compared with the prior art, the beneficial effects of the present invention are as follows: the preparation method of the palladium-based composite metal oxide semiconductor material of the present invention uses specific amounts of tin dioxide, nickel nitrate and palladium chloride as raw materials, and obtains the palladium-based composite metal oxide semiconductor material by adding an appropriate amount of urea and adopting a hydrothermal reaction combined with reduction impregnation. The preparation method is simple in process and the raw materials are easily available; the prepared palladium-based composite metal oxide semiconductor material has high hydrogen sensitivity selectivity, can quickly detect hydrogen with a low hydrogen concentration (response time 2s), and has excellent detection stability; in addition, its particle size distribution is uniform and easy to process, and can be widely used in the preparation of hydrogen sensors. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] The drawings constituting a part of the present application are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the drawings:

[0031] Figure 1 The SEM image of the palladium-based composite metal oxide semiconductor material prepared in Example 4 of the present invention is shown;

[0032] Figure 2 The selectivity test results of the palladium-based composite metal oxide semiconductor material of Example 4 are shown;

[0033] Figure 3 The selectivity test results of the composite metal oxide semiconductor material of Comparative Example 2 are shown;

[0034] Figure 4 A dynamic resistance curve of a hydrogen sensor comprising the palladium-based composite metal oxide semiconductor material of Example 4 to 500 ppb-100 ppm hydrogen at an operating temperature of 300° C.;

[0035] Figure 5 The response diagram of the hydrogen sensor comprising the palladium-based composite metal oxide semiconductor material of Example 4 at a hydrogen concentration of 100 ppm is shown;

[0036] Figure 6 A stability graph of a hydrogen sensor including the palladium-based composite metal oxide semiconductor material of Example 4 is shown. DETAILED DESCRIPTION

[0037] In order to facilitate the understanding of the present invention, the present invention will be described more comprehensively below, and preferred embodiments of the present invention are given. However, it should be understood that these embodiments are only used for more detailed description and should not be understood as limiting the present invention in any form, i.e., not intended to limit the scope of protection of the present invention.

[0038] Unless otherwise defined, the technical terms used in the following examples have the same meanings as those generally understood by those skilled in the art to which the present invention belongs. The test reagents used in the following examples are all conventional biochemical reagents unless otherwise specified; the experimental methods described are all conventional methods unless otherwise specified.

[0039] In order to further verify the technical effect of the technical solution of the present invention, it is described in detail below through specific embodiments and test examples.

[0040] Example 1

[0041] A method for preparing a palladium-based composite metal oxide semiconductor material comprises the following steps:

[0042] (1) 1100 mg of tin dichloride, 400 mg of urea, and 5 mg of nickel nitrate hexahydrate were dissolved in 20 ml of deionized water, stirred evenly, and then subjected to a hydrothermal reaction in a polytetrafluoroethylene-lined reactor at a temperature of 120° C. for 10 h; the reacted material was centrifugally washed with deionized water for 3 times, and dried at 80° C. for 12 h to obtain a composite metal oxide;

[0043] (2) The composite metal oxide is dispersed in 20 ml of deionized water, and then 11.05 mg of palladium chloride and 11.05 mg of ascorbic acid are added to react; the reacted material is centrifuged and washed three times, and dried at 80° C. for 12 h to obtain the palladium-based composite metal oxide semiconductor material; the particle size of the semiconductor material is 80-120 nm, the average particle size is 100 nm, and the particle size distribution is uniform.

[0044] Example 2

[0045] A method for preparing a palladium-based composite metal oxide semiconductor material comprises the following steps:

[0046] (1) 1100 mg of tin dichloride, 220 mg of urea, and 5 mg of nickel nitrate hexahydrate were dissolved in 20 ml of deionized water, stirred evenly, and then subjected to a hydrothermal reaction in a polytetrafluoroethylene-lined reactor at a temperature of 120° C. for 10 h; the reacted material was centrifugally washed with deionized water for 3 times, and dried at 80° C. for 12 h to obtain a composite metal oxide;

[0047] (2) The composite metal oxide is dispersed in 20 ml of deionized water, and then 33.15 mg of palladium chloride and 33.15 mg of ascorbic acid are added to react; the reacted material is centrifuged and washed three times, and dried at 80° C. for 12 h to obtain the palladium-based composite metal oxide semiconductor material; the particle size of the semiconductor material is 80-120 nm, the average particle size is 100 nm, and the particle size distribution is uniform.

[0048] Example 3

[0049] A method for preparing a palladium-based composite metal oxide semiconductor material comprises the following steps:

[0050] (1) 1100 mg of tin dichloride, 400 mg of urea, and 50 mg of nickel nitrate hexahydrate were dissolved in 20 ml of deionized water, stirred evenly, and then subjected to a hydrothermal reaction in a polytetrafluoroethylene-lined reactor at a temperature of 120° C. for 10 h; the reacted material was centrifugally washed with deionized water for 3 times, and dried at 80° C. for 12 h to obtain a composite metal oxide;

[0051] (2) The composite metal oxide is dispersed in 20 ml of deionized water, and then 23 mg of palladium chloride and 23 mg of ascorbic acid are added to react; the material after the reaction is centrifuged and washed three times, and dried at 80° C. for 12 h to obtain the palladium-based composite metal oxide semiconductor material; the particle size of the semiconductor material is 80-120 nm, the average particle size is 100 nm, and the particle size distribution is uniform.

[0052] Example 4

[0053] A method for preparing a palladium-based composite metal oxide semiconductor material comprises the following steps:

[0054] (1) 1100 mg of tin dichloride, 400 mg of urea, and 50 mg of nickel nitrate hexahydrate were dissolved in 20 ml of deionized water, stirred evenly, and then subjected to a hydrothermal reaction in a polytetrafluoroethylene-lined reactor at a temperature of 120° C. for 10 h; the reacted material was centrifugally washed with deionized water for 3 times, and dried at 80° C. for 12 h to obtain a composite metal oxide;

[0055] (2) The composite metal oxide is dispersed in 20 ml of deionized water, and then 34.5 mg of palladium chloride and 34.5 mg of ascorbic acid are added to react; the reacted material is centrifuged and washed three times, and dried at 80° C. for 12 h to obtain the palladium-based composite metal oxide semiconductor material; the particle size of the semiconductor material is 80-120 nm, the average particle size is 100 nm, and the particle size distribution is uniform. The SEM image is as follows: Figure 1 shown.

[0056] Example 5

[0057] A method for preparing a palladium-based composite metal oxide semiconductor material comprises the following steps:

[0058] (1) 1100 mg of tin dichloride, 400 mg of urea, and 50 mg of nickel nitrate hexahydrate were dissolved in 20 ml of deionized water, stirred evenly, and then subjected to a hydrothermal reaction in a polytetrafluoroethylene-lined reactor at a temperature of 120° C. for 10 h; the reacted material was centrifugally washed with deionized water for 3 times, and dried at 80° C. for 12 h to obtain a composite metal oxide;

[0059] (2) The composite metal oxide is dispersed in 20 ml of deionized water, and then 57.5 mg of palladium chloride and 57.5 mg of ascorbic acid are added to react; the reacted material is centrifuged and washed three times, and dried at 80° C. for 12 h to obtain the palladium-based composite metal oxide semiconductor material; the particle size of the semiconductor material is 80-120 nm, the average particle size is 100 nm, and the particle size distribution is uniform.

[0060] Example 6

[0061] A method for preparing a palladium-based composite metal oxide semiconductor material comprises the following steps:

[0062] (1) 1100 mg of tin dichloride, 1050 mg of urea, and 70 mg of nickel nitrate hexahydrate were dissolved in 20 ml of deionized water, stirred evenly, and then subjected to a hydrothermal reaction in a polytetrafluoroethylene-lined reactor at a temperature of 120° C. for 10 h; the reacted material was centrifugally washed with deionized water for 3 times, and dried at 80° C. for 12 h to obtain a composite metal oxide;

[0063] (2) The composite metal oxide is dispersed in 20 ml of deionized water, and then 58.5 mg of palladium chloride and 58.5 mg of ascorbic acid are added to react; the reacted material is centrifuged and washed three times, and dried at 80° C. for 12 h to obtain the palladium-based composite metal oxide semiconductor material; the particle size of the semiconductor material is 80-120 nm, the average particle size is 100 nm, and the particle size distribution is uniform.

[0064] Comparative Example 1

[0065] The preparation process, parameters and control conditions in this comparative example are the same as those in Example 1, except that this comparative example does not include step (2), that is, palladium chloride is not added. The particle size of the prepared semiconductor material is 80-120 nm, the average particle size is 100 nm, and the particle size distribution is uniform.

[0066] Comparative Example 2

[0067] The preparation process, parameters and control conditions in this comparative example are the same as those in Example 2, except that nickel nitrate is not added in step (1) of this comparative example. The particle size of the semiconductor material is 80-120 nm, the average particle size is 100 nm, and the particle size distribution is uniform.

[0068] Comparative Example 3

[0069] The preparation process, parameters and control conditions in this comparative example are the same as those in Example 3, except that tin dichloride is not added in step (1) of this comparative example. The particle size of the semiconductor material is 40-100 nm, the average particle size is 70 nm, and the particle size distribution is uniform.

[0070] Comparative Example 4

[0071] The preparation process, parameters and control conditions in this comparative example are the same as those in Example 3, except that in step (1) of this comparative example, no tin dichloride is added, and step (2) is not included, i.e., no palladium chloride is added. The particle size of the semiconductor material is 40-100 nm, the average particle size is 70 nm, and the particle size distribution is uniform.

[0072] Comparative Example 5

[0073] The present comparative example provides a method for preparing a composite metal oxide semiconductor material, specifically: 1100 mg of tin dichloride, 50 mg of nickel nitrate hexahydrate, 34.5 mg of palladium chloride, 400 mg of urea, and 34.5 mg of ascorbic acid are added to 20 ml of deionized water, stirred evenly, and added to a polytetrafluoroethylene-lined reactor, hydrothermally reacted at 120° C. for 10 hours, centrifuged and washed 5 times, and dried at 80° C. for 12 hours to obtain a composite metal oxide semiconductor material; the composite metal oxide semiconductor material has a particle size of 80-120 nm, an average particle size of 100 nm, and an uneven particle size distribution.

[0074] Comparative Example 6

[0075] The preparation process, parameters and control conditions in this comparative example are the same as those in Example 4, except that the mass of palladium chloride added in step (2) in this comparative example is 3.45 mg. The particle size of the obtained semiconductor material is 80-120 nm, the average particle size is 100 nm, and the particle size distribution is uniform.

[0076] Comparative Example 7

[0077] The preparation process, parameters and control conditions in this comparative example are the same as those in Example 4, except that the mass of palladium chloride added in step (2) in this comparative example is 69 mg. The particle size of the obtained semiconductor material is 80-120 nm, the average particle size is 100 nm, and the particle size distribution is uniform.

[0078] Comparative Example 8

[0079] The preparation process, parameters and control conditions in this comparative example are the same as those in Example 4, except that the mass of urea added in step (1) in this comparative example is 110 mg. The particle size of the prepared semiconductor material is 150-200 nm, the average particle size is 175 nm, and the particle size distribution is uniform.

[0080] Comparative Example 9

[0081] The preparation process, parameters and control conditions in this comparative example are the same as those in Example 4, except that the mass of urea added in step (1) in this comparative example is 2000 mg. The particle size of the prepared semiconductor material is 30-90 nm, the average particle size is 60 nm, and the particle size distribution is uniform.

[0082] Test Case

[0083] The palladium-based composite metal oxide semiconductor material prepared in the above embodiment and the composite metal oxide semiconductor material prepared in the comparative example are respectively applied to hydrogen sensors, and the composite metal oxide semiconductor material is configured into an aqueous solution, and the composite metal oxide semiconductor material is evenly coated on a ceramic tube electrode with a coating thickness of about 100 microns, and a heating resistance wire is configured at the same time. After heating for 24 hours to stabilize, a corresponding gas sensor is formed. The hydrogen sensitivity of the composite metal oxide semiconductor materials in different embodiments and comparative examples is characterized by the performance test of the gas sensor.

[0084] The present invention uses the Weisheng Technology WS-30A gas sensitive test platform to perform performance testing of gas sensors, wherein:

[0085] 1) The selectivity test of the composite metal oxide semiconductor material was carried out under the test environment where the heating voltage was controlled at 3V and the test voltage was 5V. The selectivity test results of the palladium-based composite metal oxide semiconductor material in Example 4 are as follows: Figure 2 , Comparative Example 4 The selectivity test results of the composite metal oxide semiconductor material are as follows Figure 3 Through comparative analysis Figure 2 and Figure 3 It can be confirmed that the technical solution of the present invention significantly improves the selectivity for hydrogen by doping an appropriate amount of palladium metal on the tin oxide and nickel oxide composite metal oxide.

[0086] 2) The test method for the detection lower limit of the composite metal oxide semiconductor material is: the injected gas is diluted to the lowest concentration in a closed environment, and the test results are shown in Table 1. Figure 4 The dynamic resistance curve of the hydrogen sensor containing the palladium-based composite metal oxide semiconductor material of Example 4 at 300°C for 500ppb-100ppm hydrogen is shown. The response value is the resistance value R of the gas sensor in the air. a and the resistance value R in the gas to be measured g The ratio of a / R g .

[0087] 3) The response time and recovery time of the composite metal oxide semiconductor material were tested under a test environment where the heating voltage was controlled at 3V and the test voltage was 5V. The test results are shown in Table 1; Figure 5 The response graph of the hydrogen sensor including the palladium-based composite metal oxide semiconductor material of Example 4 at a hydrogen concentration of 100 ppm is shown.

[0088] 4) The present invention also tests the response stability of the composite metal oxide semiconductor material: the test is carried out under a test environment where the heating voltage is controlled at 3V and the test voltage is 5V. The test results are characterized by a 30-day response stability error rate, which is calculated by the deviation from the average test result; the average test result is obtained by measuring 5 times and taking the average value. The stability test results are shown in Table 1; wherein, Figure 6 The stability test results of the hydrogen sensor including the palladium-based composite metal oxide semiconductor material of Example 4 are shown.

[0089] Table 1

[0090]

[0091] From the analysis of Examples 1-6 and Comparative Examples 1-9 in Table 1, it can be seen that the detection limit of the hydrogen sensor prepared by the palladium-based composite metal oxide semiconductor material of the present invention is 5ppb-50ppm, which is significantly lower than the hydrogen detection limit of 50-5000ppm in the comparative example, reflecting better hydrogen sensitivity performance.

[0092] From the test results of Example 1 to Example 6 in Table 1, it can be seen that the mass ratio of the tin dichloride, the nickel nitrate, and the palladium chloride described in the preparation method of the palladium-based composite metal oxide semiconductor material of the present invention is (15-100): (0.05-3): 1. Within this range, the palladium loading of the prepared palladium-based composite metal oxide semiconductor material is 0.5%-4%, and the hydrogen detection lower limit of the hydrogen sensor containing the palladium-based composite metal oxide semiconductor material of the present invention is in the range of 500ppb-50ppm, the response time is in the range of 2-28s, the recovery time is in the range of 4-30s, and the 30-day response stability error rate is controlled within 10%. Furthermore, the mass ratio of the tin dichloride, the nickel nitrate and the palladium chloride described in the preparation method of the palladium-based composite metal oxide semiconductor material of the present invention is preferably (17-50): (0.05-1.5): 1. It can be seen from the test results of Example 2 to Example 6 that within this range, the palladium loading of the prepared palladium-based composite metal oxide semiconductor material is 1.5%-4%, and the hydrogen detection lower limit of the hydrogen sensor containing the palladium-based composite metal oxide semiconductor material of the present invention is in the range of 500ppb-10ppm, the response time is in the range of 2-20s, the recovery time is in the range of 4-23s, and the 30-day response stability error rate is controlled within 10%. Furthermore, the mass ratio of the tin dichloride, the nickel nitrate and the palladium chloride described in the preparation method of the palladium-based composite metal oxide semiconductor material of the present invention is preferably (17-35): (0.5-1): 1. It can be seen from the test results of Example 2 to Example 6 that within this range, the palladium loading of the prepared palladium-based composite metal oxide semiconductor material is 2.3%-4%, and the hydrogen detection lower limit of the hydrogen sensor containing the palladium-based composite metal oxide semiconductor material of the present invention is in the range of 500ppb-5ppm, the response time is in the range of 2-10s, the recovery time is in the range of 4-16s, and the 30-day response stability error rate is controlled within 5%.

[0093] Combined analysis of Example 4 and Comparative Example 6 and Comparative Example 7: Figure 1 The SEM image of the palladium-based composite metal oxide semiconductor material prepared in Example 4 is shown. Figure 2 , Figure 4 , Figure 5 and Figure 6It is shown that the hydrogen detection lower limit of the hydrogen sensor containing the palladium-based composite metal oxide semiconductor material of Example 4 reaches 500ppb, the response time is 2s, the recovery time is 4s, and the response stability error for 30 days is controlled within 5%; when the mass of the doped palladium element is less (Comparative Example 6), the detection sensitivity of the hydrogen sensor containing the prepared semiconductor material decreases, the detection lower limit reaches 100ppm, and the response time and recovery time become longer, and the stability decreases, that is, the overall performance deteriorates; when the mass of the doped palladium element exceeds the addition range of the present invention (Comparative Example 7), the detection lower limit of the hydrogen sensor containing the prepared semiconductor material is 50ppm, and the response time, recovery time and stability are all worse than those of the embodiments of the present invention. It is speculated that excessive palladium doping hinders the overflow effect of the palladium element, thereby affecting the overall performance of the hydrogen sensor.

[0094] Combining Example 1 with Comparative Example 1, it can be confirmed that the present invention can effectively reduce the detection limit of the hydrogen sensor by doping the hydrogen-sensitive palladium element on the composite metal oxide matrix, and promote the reduction of the response time and facilitate the rapid recovery of the hydrogen sensor; Combining Example 2 with Comparative Example 2, and Figure 2 It can be verified that the present invention uses nickel oxide as one of the components of the composite metal oxide, which is beneficial to improve the hydrogen selectivity and thus improve the sensitivity of hydrogen detection, and improve the response recovery ability of the hydrogen sensor, and more importantly, improve the stability of the sensor; combined with Example 3 and Comparative Example 3, it can be confirmed that tin oxide, as one of the main components of the composite metal oxide, can improve the hydrogen sensitivity of the prepared palladium-based composite metal oxide semiconductor material and reduce the response time and recovery time, especially improve the stability of the hydrogen sensor. Combined with Example 3 and Comparative Example 4, the preparation of the palladium-based composite metal oxide semiconductor material of the present invention adopts a staged hydrothermal reaction combined with a palladium element doping operation, which significantly improves the hydrogen sensitivity of the prepared palladium-based composite metal oxide semiconductor material compared to the one-pot preparation method of tin dichloride, nickel nitrate, and palladium chloride, and effectively reduces the response time and recovery time, and the stability is also improved by more than 6 times, which confirms that the specific preparation process of the present invention improves the hydrogen sensitivity comprehensive performance of the prepared palladium-based composite metal oxide semiconductor material.

[0095] This verifies that the preparation method of the palladium-based composite metal oxide semiconductor material of the present invention optimizes the mass ratio of the added tin dichloride, nickel nitrate and palladium chloride, so that the prepared palladium-based composite metal oxide semiconductor material is loaded with an appropriate and small amount of palladium metal, thereby achieving the technical effect of reducing the lower limit of hydrogen detection and improving the detection stability of the hydrogen sensor.

[0096] Combining Example 4 with Comparative Examples 8 and 9, it can be verified that adding an appropriate amount of urea with a mass of 0.2-1 times the mass of tin dichloride in the hydrothermal reaction stage of the preparation method of the palladium-based composite metal oxide semiconductor material of the present invention can act as a structure directing agent and reaction regulator in the early stage of the hydrothermal reaction, guiding the formation of a specific composite metal oxide nanostructure; and decomposing and evaporating after the hydrothermal reaction, so that the composite metal oxide forms a specific porous structure to provide more gas adsorption sites, and ultimately improve the hydrogen detection sensitivity of the prepared palladium-based composite metal oxide semiconductor material. When the amount of urea added in the step (1) is too small (Comparative Example 8, the amount of urea added is 0.1 times the mass of tin dichloride), the composite metal oxide cannot be promoted to form a specific porous structure, thereby resulting in the lower limit of hydrogen detection of the prepared palladium-based composite metal oxide semiconductor material being only 1000ppm, the response time and the recovery time reaching 103s and 115s respectively, and the 30-day error rate reaching 30%, and the overall performance is poor; when the amount of urea added in the step (1) is too large (Comparative Example 9, the amount of urea added is 1.82 times the mass of tin dichloride), considering that excessive urea affects the pH value of the reaction system or causes the pore structure of the composite metal oxide to be too large or uneven, thereby affecting the stability of the prepared palladium-based composite metal oxide semiconductor material, the lower limit of hydrogen detection of the composite semiconductor material in Comparative Example 9 is 50ppm, the response time and the recovery time are 30s and 37s respectively, and the 30-day error rate also reaches 15%, and the overall performance is worse than that of Example 4. Therefore, in the preparation method of the palladium-based composite metal oxide semiconductor material of the present invention, the mass ratio of tin dichloride to the urea is 1: (0.2-1); preferably 1: (0.3-0.5). The porous structure of the composite metal oxide formed by adding urea within this range can promote the improvement of the comprehensive hydrogen-sensitive performance of the prepared palladium-based composite metal oxide semiconductor material.

[0097] In summary, compared with comparative examples 1-9, the palladium-based composite metal oxide semiconductor material of the present invention has better hydrogen sensitivity, faster response rate, and higher stability, and is more efficient and safe for hydrogen detection.

[0098] It should be noted that the above contents are further detailed descriptions of the present invention in combination with specific implementation methods, and it cannot be determined that the specific implementation of the present invention is limited to these descriptions. For ordinary technicians in the technical field to which the present invention belongs, several simple improvements can be made without departing from the concept of the present invention, which should be regarded as falling within the scope of protection of the present invention.

Claims

1. A method for preparing a palladium-based composite metal oxide semiconductor material, characterized in that: The following steps are involved: (1) separating and drying the materials after hydrothermal reaction of tin dichloride, urea and nickel nitrate in deionized water to obtain a composite metal oxide; (2) dispersing the composite metal oxide in deionized water, and then adding palladium chloride and a reducing agent to react; the reacted material is separated and dried to obtain the palladium-based composite metal oxide semiconductor material; Wherein, the mass ratio of the tin dichloride, the nickel nitrate and the palladium chloride is (17-100): (0.05-3):1; the mass ratio of the tin dichloride to the urea is 1:(0.2-1).

2. The method for preparing a palladium-based composite metal oxide semiconductor material according to claim 1, wherein: The mass ratio of the tin dichloride, the nickel nitrate and the palladium chloride is (17-50):(0.05-1.5):

1.

3. The method for preparing a palladium-based composite metal oxide semiconductor material according to claim 2, wherein: The mass ratio of the tin dichloride, the nickel nitrate and the palladium chloride is (17-35):(0.5-1):

1.

4. The method for preparing a palladium-based composite metal oxide semiconductor material according to claim 1, characterized in that: The mass ratio of the palladium chloride to the reducing agent is 1:(0.5-3); And / or, the reducing agent is ascorbic acid or sodium borohydride.

5. The method for preparing a palladium-based composite metal oxide semiconductor material according to claim 1, characterized in that: The mass ratio of the tin dichloride to the urea is 1:(0.2-0.5).

6. The method for preparing a palladium-based composite metal oxide semiconductor material according to claim 1, characterized in that: The temperature of the hydrothermal reaction in step (1) is 100-150° C., and the reaction time is 10-15 hours.

7. The method for preparing a palladium-based composite metal oxide semiconductor material according to claim 1, characterized in that: The reaction in step (2) is carried out under stirring conditions, the reaction temperature is 15-30° C., and the reaction time is 5-10 h.

8. A palladium-based composite metal oxide semiconductor material, characterized in that: The palladium-based composite metal oxide semiconductor material is prepared by the preparation method described in any one of claims 1 to 7.

9. The palladium-based composite metal oxide semiconductor material according to claim 8, characterized in that: The palladium loading in the palladium-based composite metal oxide semiconductor material is 0.5%-4%.

10. The palladium-based composite metal oxide semiconductor material according to claim 8, characterized in that: The average particle size of the composite metal oxide semiconductor material is 80-120 nm.

11. A hydrogen sensor comprising the palladium-based composite metal oxide semiconductor material according to any one of claims 8 to 10.

12. The hydrogen sensor according to claim 11, characterized in that: The hydrogen sensor is obtained by coating a mixed slurry containing the palladium-based composite metal oxide semiconductor material on the outer wall of a ceramic tube having an electrode and drying the mixture; wherein the mixed slurry is obtained by dispersing the palladium-based composite metal oxide semiconductor material in deionized water.

13. The hydrogen sensor according to claim 12, characterized in that: The coating thickness of the palladium-based composite metal oxide semiconductor material is 50-150 μm.

Citation Information

Patent Citations

  • Preparation method and application of palladium / nickel alloy-supported graphene material

    CN109433225A

  • Preparation method and application of NiO-SnO2 composite material with flower-like structure

    CN112320859A

  • Hydrogen MEMS sensor for power battery detection and preparation method thereof

    CN115078461A

  • Preparation method of PdPt / SnO2 (at) ZIF-8 gas-sensitive composite material and hydrogen sensing application of PdPt / SnO2 (at) ZIF-8 gas-sensitive composite material

    CN117054492A

  • Semiconductor-type ammonia gas sensor and its manufacture

    JP1995103925A